Age Variations in Risk Perceptions and Smoking Decisions - Viscusi, W. Kip (The Review of Economics and Statistics, 1991)
The results of a numerical survey of smoking risks and behavior are analyzed. Smoking risk perceptions follow the expected patterns given age differences in risk information acquired and differences in information associated with smoking status. Risk perceptions are greater as one moves to younger age cohorts where overall lung cancer risks are substantially overestimated. These risk perceptions in turn have a negative effect on smoking decisions, where younger individuals behave no differently in terms of the manner in which they incorporate risk perceptions into their smoking decisions. Copyright 1991 by MIT Press.